2020
DOI: 10.26442/00403660.2020.12.200433
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of small bowel bacterial overgrowth in patients with functional dyspepsia: a meta-analysis

Abstract: Aim.Systematization of data on the frequency of detection of the syndrome of bacterial overgrowth in the small intestine (SIBO) in patients with functional dyspepsia (FD). Materials and methods.MEDLINE/PubMed, EMBASE, Cochrane, Google Scholar, the Russian Science Citation Index (RSCI) through July 2020 were searched to identify studies evaluating the prevalence of SIBO in FD. In addition, a search for relevant abstracts was carried out in the electronic databases of the United European Gastroenterology W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
(67 reference statements)
0
2
0
1
Order By: Relevance
“…Несмотря на гетерогенность паттерна моторных нарушений, общими для большинства ФЗ ЖКТ являются связь симптоматики с тревогой и депрессией, наличие висцеральной гиперчувствительности, нередкий постинфекционный генез заболевания, изменения микробиоты ЖКТ (ассоциация с синдромом избыточного бактериального роста в тонкой кишке), повышение проницаемости слизистой оболочки кишечника и воспаление слизистой оболочки низкой степени активности (от англ. low-grade inflammation) [22][23][24][25][26][27]. Эффективная фармакотерапия ФЗ ЖКТ остается трудной задачей в условиях рутинной клинической практики, так как у многих пациентов наблюдается субоптимальный комплаенс, что диктует необходимость использования лекарственных форм препаратов с большей дозой действующего вещества или пролонгированным высвобождением [18,28].…”
Section: Discussionunclassified
“…Несмотря на гетерогенность паттерна моторных нарушений, общими для большинства ФЗ ЖКТ являются связь симптоматики с тревогой и депрессией, наличие висцеральной гиперчувствительности, нередкий постинфекционный генез заболевания, изменения микробиоты ЖКТ (ассоциация с синдромом избыточного бактериального роста в тонкой кишке), повышение проницаемости слизистой оболочки кишечника и воспаление слизистой оболочки низкой степени активности (от англ. low-grade inflammation) [22][23][24][25][26][27]. Эффективная фармакотерапия ФЗ ЖКТ остается трудной задачей в условиях рутинной клинической практики, так как у многих пациентов наблюдается субоптимальный комплаенс, что диктует необходимость использования лекарственных форм препаратов с большей дозой действующего вещества или пролонгированным высвобождением [18,28].…”
Section: Discussionunclassified
“…A meta-analysis of seven studies found that the prevalence of SIBO in functional dyspepsia is 34.7% (95%CI: 24.8%-45.4%)[ 26 ]. Another meta-analysis found SIBO prevalence in functional dyspepsia to be significantly higher using the LBT (53.4%, 95%CI: 33.9%-71.9%) compared with the GBT (17.2%, 95%CI: 8.6%-31.6%).…”
Section: Functional Digestive Diseasesmentioning
confidence: 99%
“…In a meta-analysis of 7 studies involving 1248 patients, the pooled incidence of SIBO in patients with FD was 34.73% (95% CI: 24.807-45.380). When a study that examined the incidence of SIBO in patients with refractory FD was excluded from the metaanalysis, the pooled prevalence was 38.98% (95% CI: 28.964-49.490) [11].…”
mentioning
confidence: 99%